(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
Transcript of the introduction to a Seminar and Launch on 22 September 2017 at the University of Edinburgh Today’s seminar is both a launch of the Community Engagement: A Critical Guide for Practitioners and an opportunity to consider the problematic nature of community engagement in practice. It is not an information or motivational day on how to do community engagement; nor a decision-making or strategy-forming forum, though it may provoke some follow up activity. Neither is it representative of any particular interests or arguments.It is intended as a forum for questioning, critique and the expression of constructive skepticism; a chance for people to come together in what we hope will be a stimulating and convivial atmosphere; an opportunity to meet friends, old and new, and allies – to feel refreshed and renewed.